Desirable leadership attributes are preferentially associated with women: A quantitative study of gender and leadership roles in the Australian workforce. Issue 1 (February 2019) - Griffiths, Oren; Roberts, Lynette; Price, Josh
Women are under-represented globally in leadership roles. One theory suggests that this imbalance is due to a mismatch between the qualities women are perceived to have, and the qualities desired in business leaders. Yet, little is known about whether this incongruence remains prevalent in the Australian business environment. To this end, this study investigated gender stereotypes and desired leadership attributes in 1885 participants from 25 companies using a priopietary measure developed by a local diversity consulting company. Participants ranked the attributes that they believed were most important for leadership and rated the degree to which each attribute was associated with men or women. Men were more strongly associated with some agentic traits, whereas women were more strongly associated with a diverse range of both agentic and communal traits. Desired leadership qualities included both agentic and communal qualities, but generally favoured traits associated with women. JEL Classification:J16, M12